Silicon-Based MOEMS and Their Applications - Harald Schenk; Wibool Piyawattanametha (My University, 2008)
The Journal of Micro/Nanopatterning, Materials, and Metrology (JM3) publishes peer-reviewed papers on the core enabling technologies that address the patterning needs of the electronics industry.
Keywords: Advanced Surface Polishing Techniques